Cloud Computing Knowledge-Based Framework for Information Access and Use in an Open University Library - Okwoli, Mercy Enefu (Communicate: Journal of Library and Information Science, 2023)
The A cloud computing technology-based framework for information access and use in an open university library was investigated in this study. Issues concerning the information services provided by the National Open University of Nigeria library, such as building a digital library, searching library data, building community power, and the implications of cloud computing in terms of cost, staff, and maintenance, were investigated. The study’s objectives include, among other things, determining how the National Open University of Nigeria library provides information services and access to its students spread across the country. Two research objectives were proposed: the information services provided by cloud computing in the National Open University of Nigeria library and the cost implications of cloud computing.